TINGKAT EFISIENSI PERBANKAN SYARIAH DAN KONVENSIONAL DENGAN MENGUNAKAN DATA ENVELOPMENT ANALYSIS (DEA) - Nico Ferari; Heri Sudarsono (Faculty of Economics, Universitas Islam Indonesia, 2011)
This research utilizesa non-parametric frontier approach, Data Envelopment Analysis (DEA). By using such an analysis, the purpose of this study is to analyse 3 Islamic banks in Indonesia during 2007-2010 period. In general, the result of study indicates that the level of efficiency of Islamic bank is various moving over time. In intermediary efficiency, conventional bank is found to be more efficient than Islamic bank. Moreover, conventional bank is more efficient than Islamic bank. Since the study pinpoints the sources of inefficiency, it also helps to provide the banks with strategic planning